Neuronal Porosome-The Secretory Portal at the Nerve Terminal: It’s Structure-Function, Composition, and Reconstitution - Jena, Bhanu P. (J Mol Struct, 2014)
Cup-shaped secretory portals at the cell plasma membrane called porosomes mediate secretion from cells. Membrane bound secretory vesicles transiently dock and fuse at the cytosolic compartment of the porosome base to expel intravesicular contents to the outside during cell secretion. In the past decade, the structure, isolation, composition, and functional reconstitution of the neuronal porosome complex has been accomplished providing a molecular understanding of its structure-function. Neuronal porosomes are 15 nm cup-shaped lipoprotein structures composed of nearly 40 proteins. Being a membrane-associated supramolecular complex has precluded determination of the atomic structure of the porosome. However recent studies using small-angle X-ray solution scattering (SAXS), provide at sub-nanometer resolution, the native 3D structure of the neuronal porosome complex associated with docked synaptic vesicle at the nerve terminal. Additionally, results from the SAXS study and earlier studies using atomic force microscopy, provide the possible molecular mechanism involved in porosome-mediated neurotransmitter release at the nerve terminal.